Molecular Characterization and Phylogenetic Analysis of Listeria monocytogenes Isolated from Milk and Milk Products in Kaduna, Nigeria. (11th August 2016) - Usman, U. B.; Kwaga, J. K. P.; Kabir, J.; Olonitola, O. S.; Radu, S.; Bande, F.
Abstract : In this study, Listeria ( L. ) monocytogenes isolated from milk and milk products in Kaduna, Nigeria, were subjected to a multiplex PCR assay to identify virulence-associated genes (such as prf A, inl A, hly A, act A, and iap ). Of the 36 isolates, 9 (25%) were positive for one or two virulence-associated genes. Based on the sample type, 6 (16.9%) of the isolates that possessed virulence-associated genes were obtained from raw milk, 2 (3.2%) from "Manshanu, " and 1 (2.8%) from "Kindrimo." Sequence and phylogenetic analysis based on the 16S rRNA revealed that Nigerian L. monocytogenes isolates (NGA 34A, NGA 35A, NGA 41A, and NGA 38A), when compared with reference L. monocytogenes, were grouped into two distinct clusters, A and B, with sequence (NGA 34A, NGA 35A, and NGA 41A) phylogenetically closer to J1776; N1-011A; R2-502; J1816; and J2-031, whereas L. monocytogenes isolate (NGA 38A) clustered with EDG; J1-220; J1926; J1817; and J2-1091. The separation of the Nigerian L. monocytogenes isolates into linage A (responsible for epidemic listeriosis) and lineage B (responsible for sporadic cases of listeriosis) is of public health concern and that local isolates might have potentials for human food borne listeriosis based on the virulence factors so far identified.